Soft magnetic material and method for producing same

By optimizing the Fe and Si content in Fe-based nanocrystalline soft magnetic materials and using a rapid heat treatment process, the problem of high saturation flux density and low coercivity is solved, and the preparation of high-performance soft magnetic materials is realized.

CN119811819APending Publication Date: 2025-04-11TOYOTA JIDOSHA KK
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411399354.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-10
Filing Date
2024-10-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art is difficult to have both high saturation flux density and low coercivity in soft magnetic materials, especially in Fe-based nanocrystalline soft magnetic materials, and it is difficult to maintain high saturation flux density and suppress the coarseness of the crystalline phase.

Method used

By rapidly heat treatment of an alloy with an amorphous phase with a principal component Fe and containing an appropriate amount of Si, Fe is generated with a Fe-based nanocrystalline soft magnetic material with high saturation flux density and low coercivity. The specific process includes preparing an amorphous alloy with a specific composition, heating it to a temperature range of 485°C to 500°C at a temperature increase of 100°C/sec or above, and maintaining it to a quench cooler after 0 to 80 seconds.

Benefits of technology

It realizes high saturation flux density and low coercivity of soft magnetic materials used in magnetic components such as motors and reactors, and is suitable for the manufacturing of high-performance magnetic cores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119811819A_ABST
    Figure CN119811819A_ABST
Patent Text Reader

Abstract

The invention relates to a soft magnetic material and a manufacturing method thereof. Provided are a soft magnetic material having both a high saturation magnetic flux density and a low coercive force, and a method for producing the soft magnetic material. A soft magnetic material according to the present invention is a soft magnetic material represented by the compositional formula Fe100-x-y-z-wBxNiySizMw, in which M is one or more unavoidable elements selected from the group consisting of Nb, Mo, Ta, W, Co and Sn, and x, y, z and w satisfy, in atomic%, 12 < = x < = 17, 1 < = y < = 3, 0 lt; z < = 1, 0lt; w < = 0.1, the soft magnetic material contains an alpha-Fe phase, the alpha-Fe phase contains crystals having an average particle diameter of 30 nm or less, and the average particle diameter of the crystals is the average value of the projected area equivalent circle diameter of the crystals in a transmission electron microscope (TEM) image of the soft magnetic material flaked by a focused ion beam (FIB). The ratio of the peak area of the crystalline (211) plane of the alpha-Fe phase on the surface of the soft magnetic material to the total peak area as determined by XRD is 0.10 or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a soft magnetic material and a method for manufacturing the same. Background Art

[0002] In order to improve the performance of components such as motors and reactors, it is required that the soft magnetic material for the core part of such components has both a high saturation magnetic flux density (high torque) and a low coercive force (low loss).

[0003] Examples of soft magnetic materials having a high saturation magnetic flux density include electromagnetic steel sheets, Fe-based nanocrystalline soft magnetic materials, etc. The so-called Fe-based nanocrystalline soft magnetic material refers to a soft magnetic material whose main component is Fe and in which nanocrystals are dispersed.

[0004] For example, Patent Document 1 describes an Fe-based soft magnetic alloy characterized by being represented by the general formula Fe 100-a-b-c-d-e Ni a M b B c M' d M" e (wherein, M represents one or more elements selected from Si, Ge, and Ga, M' represents one or more elements selected from Nb, Mo, W, Ta, Zr, Hf, and Ti, M" represents one or more elements selected from V, Cr, and Mn, a, b, c, d, and e represent atomic percentages and respectively satisfy 0.5 ≤ a ≤ 5, 0 ≤ b ≤ 10, 9 ≤ c ≤ 16, 1 ≤ d ≤ 6, 0 ≤ e ≤ 2, and 16 ≤ a + b + c + d + e ≤ 25).

[0005] Patent Document 2 describes a method for manufacturing a soft magnetic material, which includes the following steps: preparing an alloy having a composition represented by the following Composition Formula 1 or Composition Formula 2 and having an amorphous phase; and heating the alloy at a heating rate of 10 °C / second or more, and holding it at a temperature above the crystallization start temperature and less than the Fe-B compound generation start temperature for 0 to 80 seconds. The Composition Formula 1 is Fe 100-x-y B x M y , M is at least one element selected from Nb, Mo, Ta, W, Ni, Co, and Sn, and x and y satisfy 10 ≤ x ≤ 16 and 0 ≤ y ≤ 8 in atomic percentages. The Composition Formula 2 is Fe 100-a-b- c B a Cu b M' c , M' is at least one element selected from Nb, Mo, Ta, W, Ni, and Co, and a, b, and c satisfy 10 ≤ a ≤ 16, 0 < b ≤ 2, and 0 ≤ c ≤ 8 in atomic percentages.

[0006] Prior Art Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 6-41698

[0008] Patent Document 2: Japanese Patent Application Publication No. 2018-22797 Summary of the invention

[0009] In order to improve the performance of magnetic components such as motors and reactors, it is important that the soft magnetic material of the core portion has both high saturation magnetic flux density and low coercive force as described above.

[0010] Fe-based nanocrystalline soft magnetic materials have high saturation flux density because their main component is Fe. Fe-based nanocrystalline soft magnetic materials are obtained by heat treating (also called "annealing") an alloy having an amorphous phase. If the Fe content in the amorphous alloy is high, a crystalline phase (α-Fe) is easily generated from the amorphous phase during heat treatment, and the crystalline phase is prone to grain growth and thus coarsening. Therefore, an element that inhibits grain growth is added to the material. However, since the Fe content in the material decreases in response to the addition of the element, the saturation flux density of the material decreases. Therefore, in a soft magnetic material whose main component is Fe, it is difficult to maintain a high saturation flux density and suppress the coarsening of the crystalline phase during heat treatment to maintain a low coercive force.

[0011] Therefore, an object of the present invention is to provide a soft magnetic material having both high saturation magnetic flux density and low coercive force, and a method for producing the same.

[0012] The inventors have conducted various studies on means for solving the above-mentioned problems, and as a result, have found that by rapidly heat treating an alloy having an amorphous phase whose main component is Fe and which contains Si in an appropriate amount, an Fe-based nanocrystalline soft magnetic material that maintains a low coercive force and has a high saturation magnetic flux density can be obtained, thereby completing the present invention.

[0013] That is, the gist of the present invention is as follows.

[0014] (1) A soft magnetic material having the following composition formula: Fe 100-x-y-z-w B x Ni y Si z M wA soft magnetic material represented by (where M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w satisfy 12 ≤ x ≤ 17, 1 ≤ y ≤ 3, 0 < z ≤ 1, 0 < w ≤ 0.1 in atomic %), the soft magnetic material contains an α-Fe phase, the α-Fe phase contains crystals with an average particle size of 30 nm or less, the average particle size of the crystals is the average value of the projected area equivalent circle diameters of the crystals in the transmission electron microscope (TEM) image of the soft magnetic material thinned by focused ion beam (FIB), and the ratio (crystalline (211) plane peak area / XRD peak total area) of the peak area of the crystalline (211) plane of the crystalline substance measured by XRD on the surface of the α-Fe phase of the soft magnetic material to the total area of the peaks (XRD peak total area) is 0.10 or more.

[0015] (2) The soft magnetic material according to (1), 0.2 ≤ z ≤ 0.9.

[0016] (3) A method for manufacturing a soft magnetic material, comprising the following steps:

[0017] Prepare an alloy having the following composition formula: Fe 100-x-y-z-w B x Ni y Si z M w (where M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w satisfy 12 ≤ x ≤ 17, 1 ≤ y ≤ 3, 0 < z ≤ 1, 0 < w ≤ 0.1 in atomic %), and having an amorphous phase; and

[0018] Perform rapid heat treatment on the alloy in such a way that the arrival temperature of the alloy is in the temperature range above the crystal formation start temperature of the α-Fe phase and less than the Fe-B compound formation start temperature.

[0019] (4) The manufacturing method according to (3), in the rapid heat treatment, the arrival temperature of the alloy is 485 °C to 500 °C.

[0020] (5) The manufacturing method according to (3) or (4), in the rapid heat treatment, the heating rate of the alloy is 100 °C / second to 415 °C / second.

[0021] (6) The manufacturing method according to any one of (3) to (5), in the rapid heat treatment, the holding time of the alloy is 0 seconds to 80 seconds.

[0022] (7) The manufacturing method according to any one of (3) to (6), the rapid heat treatment is carried out by sandwiching the alloy between heated blocks.

[0023] According to the present invention, a soft magnetic material having both a high saturation magnetic flux density and a low coercive force and a method for manufacturing the same can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a graph showing the relationship between the Si content and the peak area ratio of the crystalline (211) plane or the saturation magnetic flux density in Example 5 and Comparative Examples 5 to 6.

[0025] Figure 2 It is a graph showing the relationship between the heat treatment temperature and the saturation magnetic flux density in Examples 1 to 7 and Comparative Examples 1 to 4.

[0026] Figure 3 It is a graph showing the relationship between the peak area ratio of the crystalline (211) plane and the saturation magnetic flux density in Examples 1 to 7 and Comparative Examples 1 to 4. DETAILED DESCRIPTION OF THE INVENTION

[0027] Hereinafter, preferred embodiments of the present invention will be described in detail.

[0028] In this specification, the features of the present invention will be described with appropriate reference to the drawings. The soft magnetic material and the manufacturing method thereof according to the present invention are not limited to the following embodiments, and can be implemented in various ways obtained by making changes, improvements, etc. that those skilled in the art can make without departing from the gist of the present invention.

[0029] Furthermore, in this specification and the like, a range expressed as "numerical value to numerical value" means a range including the numerical value.

[0030] (Soft magnetic material)

[0031] The soft magnetic material of the present invention has the following compositional formula: Fe 100-x-y-z-w B x Ni y Si z M w (In the formula, M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w satisfy 12 ≤ x ≤ 17, 1 ≤ y ≤ 3, 0 < z ≤ 1, 0 < w ≤ 0.1 in atomic %) represents an Fe-based nanocrystalline soft magnetic material.

[0032] During the manufacturing process of the soft magnetic material of the present invention, the composition of the amorphous alloy generally does not change. Therefore, the composition of the soft magnetic material of the present invention is the same as the composition of the amorphous alloy used for manufacturing.

[0033] In the soft magnetic material of the present invention, the main component is Fe, and the content of Fe is more than 50 atomic % of the total composition. Therefore, 100-xyzw representing the content of Fe is more than 50 atomic %, and from the viewpoint of having a high saturation magnetic flux density, it is more than 80 in one embodiment, and more than 85 in one embodiment.

[0034] The x representing the content of B (boron) is 12 to 17 in atomic %, and in one embodiment, 12 to 14.

[0035] The soft magnetic material of the present invention contains B in the above range, and while ensuring the Fe content, it is present between α-Fe crystals to suppress the grain growth of α-Fe, thereby reducing the coercive force of the soft magnetic material.

[0036] y indicating the content of Ni is 1 to 3 in atomic %, and in one embodiment, is 1.5 to 2.5.

[0037] The soft magnetic material of the present invention contains Ni in the above-mentioned range, so that the magnitude of the induced magnetic anisotropy can be controlled.

[0038] The content of Si represented by z is in the range of greater than 0 and 1 in atomic %, and is 0.2 to 0.9 in one embodiment, and 0.5 to 0.9 in another embodiment.

[0039] The soft magnetic material of the present invention contains Si in the above range, so that the peak area ratio of the (211) plane of the α-Fe phase on the surface of the soft magnetic material measured by XRD (X-Ray Diffraction) can be increased.

[0040] W, which represents the content of M, i.e., the inevitable element, is in the range of greater than 0 and less than 0.1 in terms of atomic %, and in one embodiment, is in the range of greater than 0 and less than 0.05. In addition, the so-called inevitable elements refer to impurities contained in raw materials, which cannot be avoided or whose avoidance will significantly increase the manufacturing cost.

[0041] The soft magnetic material of the present invention contains the inevitable elements within the above-mentioned range, and thus can suppress a decrease in saturation magnetic flux density due to an increase in the inevitable elements.

[0042] Furthermore, in order to improve corrosion resistance, inhibit grain growth, and increase nucleation frequency, the soft magnetic material of the present invention may also contain one or more elements selected from, for example, Zr, Hf, Cu, Ag, Au, Zn, As, Sb, Bi, Y and rare earth elements within a range that does not significantly reduce the saturation magnetic flux density.

[0043] In the soft magnetic material of the present invention, the ratio of the peak area of ​​the (211) face of the crystalline α-Fe phase on the surface of the soft magnetic material measured by XRD (crystalline (211) face peak area) to the area of ​​the total peak (XRD peak total area) (crystalline (211) face peak area / XRD peak total area, hereinafter also referred to as "crystalline (211) face peak area ratio") is 0.10 or more, in one embodiment 0.100 or more, in one embodiment 0.102 or more, in one embodiment 0.105 or more. The crystalline (211) face peak area ratio is not limited but is generally 0.13 or less, in one embodiment 0.12 or less.

[0044] Here, as is well known in the art, the peaks of the α-Fe phase on the surface of the soft magnetic material measured by XRD include the peaks of the (110) plane, (200) plane, (211) plane, (220) plane, and (310) plane. Moreover, the (110) plane and the (211) plane have crystalline peaks and amorphous peaks (halo peaks), respectively. Therefore, the crystalline (211) plane peak area ratio in the present invention means the ratio of the peak area of ​​the crystalline (211) plane observed by XRD to the total area of ​​all peaks, i.e., the peaks of the crystalline (110) plane, the amorphous (110) plane, the (200) plane, the crystalline (211) plane, the amorphous (211) plane, the (220) plane, and the (310) plane.

[0045] The crystalline (211) plane peak area ratio can be calculated as follows.

[0046] (1) XRD is used to measure the X-ray diffraction pattern of soft magnetic materials.

[0047] (2) The obtained X-ray diffraction pattern is normalized by the peak of the (110) plane having the maximum intensity.

[0048] (3) For each peak, the background (BG) was approximated by a straight line using the average value of 10 points at both ends of the following 2θ range: 30° to 60° for the (110) plane, 60° to 70° for the (200) plane, 70° to 92° for the (211) plane, 94° to 102° for the (220) plane, and 112° to 120° for the (310) plane.

[0049] (4) For each peak after subtracting BG, the split-type Pearson VII function is used to perform peak fitting of the crystalline peak and the amorphous peak, and the areas of Kα1 and Kα2 of each peak are calculated. Furthermore, in the soft magnetic material of the present invention, halo peaks originating from amorphous are confirmed on the (110) plane and the (211) plane. Therefore, for the (110) plane and the (211) plane, Kα1 and Kα2 of crystalline and Kα1 and Kα2 of amorphous are observed, respectively.

[0050] (5) The crystalline (211) plane peak area ratio was calculated by dividing the Kα1 peak area of ​​the crystalline (211) plane by the sum of the Kα1 peak areas of each peak.

[0051] The crystalline (211) plane peak area ratio of the soft magnetic material of the present invention being within the above range means that in the soft magnetic material of the present invention, there are grains of anisotropic growth (consistent crystal orientation) of a specific crystal plane of the α-Fe phase, namely the (211) plane. Such grains bring about low coercivity (low loss) and high saturation flux density (high torque) of the soft magnetic material.

[0052] The soft magnetic material of the present invention contains 30 volume % or more of α-Fe phase crystals, and in one embodiment contains 60 volume % or more of α-Fe phase crystals based on the total volume of the soft magnetic material.

[0053] The average particle size of the α-Fe phase crystals contained in the soft magnetic material of the present invention is less than 30nm. Furthermore, the average particle size of the α-Fe phase crystals is not limited but is generally greater than 10nm. Here, the average particle size of the α-Fe phase crystals is calculated by the following steps: (1) thinning the soft magnetic material using a focused ion beam (FIB), (2) observing a sample of the thinned soft magnetic material using a transmission electron microscope (TEM), (3) randomly selecting any number of more than 100 crystals from the α-Fe phase of the TEM image, (4) measuring the projected area equivalent circle diameter (Heywood diameter) of the selected crystals as the particle size, and (5) averaging the obtained particle sizes.

[0054] When the average grain size of the α-Fe phase crystals contained in the soft magnetic material of the present invention is within the above range, a high saturation magnetic flux density and a low coercive force of the soft magnetic material can be achieved.

[0055] When the soft magnetic material of the present invention is in the form of a thin ribbon, the average thickness of the soft magnetic material of the present invention is not limited, but is usually 10 μm to 25 μm, and in one embodiment, 15 μm to 30 μm.

[0056] By setting the thickness of the soft magnetic material of the present invention to be within the above range, the loss can be reduced.

[0057] The saturation magnetic flux density of the soft magnetic material of the present invention is usually 1.850 T or more, and in one embodiment, is 1.855 T or more, for example, 1.850 T to 1.900 T, and in one embodiment, is 1.855 T to 1.900 T.

[0058] The coercive force of the soft magnetic material of the present invention is usually 20 A / m or less, and in one embodiment, 12 A / m or less, for example, 5 A / m to 20 A / m, and in one embodiment, 7.0 A / m to 12 A / m.

[0059] The soft magnetic material of the present invention has both high saturation magnetic flux density and low coercive force, and can be used as a magnetic core of electronic components such as motors and reactors.

[0060] (Method for producing soft magnetic material)

[0061] The soft magnetic material of the present invention can be produced by a method known in the art, such as the method described in Japanese Patent Application Publication No. 2019-206746, except that an appropriate amount of Si is contained in the raw material alloy and the alloy is rapidly heat treated.

[0062] Hereinafter, an example of the method for producing the soft magnetic material of the present invention will be described.

[0063] (Preparation process of amorphous alloy)

[0064] First, an alloy having an amorphous phase is prepared. The alloy having an amorphous phase is a raw material of the soft magnetic material of the present invention having the same composition as the soft magnetic material of the present invention as described above, and its main component is Fe.

[0065] In the present invention, "Fe is the main component" means that the content of Fe in the material is 50 atomic % or more. "Alloy having an amorphous phase" means that an amorphous phase of 50 volume % or more is present in the alloy, and it is sometimes referred to as "amorphous alloy". "Alloy" has the form of thin strips, flakes, granules, blocks, etc.

[0066] From the viewpoint of obtaining many fine crystalline phases by rapid thermal treatment, the content of the amorphous phase in the amorphous alloy is 60 volume % or more in one embodiment, and 85 volume % or more in another embodiment.

[0067] The amorphous alloy is obtained by rapidly cooling a molten metal whose main component is Fe. When the molten metal is rapidly cooled, B promotes the formation of an amorphous phase. By making the content of B (residual amount of B) of the amorphous alloy obtained by rapidly cooling the molten metal more than 12 atomic % of the total composition, the main phase of the amorphous alloy can be an amorphous phase. On the other hand, by making the content of B of the amorphous alloy less than 17 atomic % of the total composition, the amount of Fe required for a high saturation magnetic flux density can be ensured, and the formation of Fe-B compounds when the amorphous phase is crystallized can be avoided.

[0068] The amorphous alloy contains Ni. By containing Ni in the amorphous alloy, the magnitude of the induced magnetic anisotropy can be controlled. From the viewpoint that the effect becomes clear, the content of Ni is more than 1 atomic % of the total composition. On the other hand, if the content of Ni is less than 3 atomic % of the total composition, Fe and B, which are other essential elements of the amorphous alloy, will not become too small, and as a result, the soft magnetic material obtained by rapid heat treatment of the amorphous alloy can have both high saturation flux density and low coercive force.

[0069] In the amorphous alloy, part of B is replaced by Si.

[0070] It is known that Si is an element responsible for amorphous formation, and by adding Si, the temperature of Fe-B compounds with large crystal magnetic anisotropy can be increased, so that the heat treatment temperature is increased. In the present invention, it is found that by making Si an appropriate amount, that is, a range greater than 0 atomic % and less than 1 atomic % of the total composition, in one embodiment, 0.2 atomic % to 0.9 atomic % and in one embodiment, 0.5 atomic % to 0.9 atomic % is different from the previous teachings, the anisotropic growth of the crystal of the α-Fe phase, that is, the growth of the (211) plane of the crystal of the α-Fe phase can be promoted by heat treatment, and a high saturation magnetic flux density is exhibited.

[0071] Furthermore, Si has the effect of reducing the viscosity of the melt, facilitating the melt discharge, and suppressing nozzle clogging.

[0072] In the amorphous alloy, in the composition formula, one or more inevitable elements selected from the group consisting of Nb, Mo, Ta, W, Co and Sn are contained.

[0073] In addition, in order to improve corrosion resistance, inhibit grain growth, and increase nucleation frequency, the amorphous alloy may also contain one or more elements selected from, for example, Zr, Hf, Cu, Ag, Au, Zn, As, Sb, Bi, Y and rare earth elements within a range that does not significantly reduce the saturation magnetic flux density.

[0074] Next, the method for manufacturing an amorphous alloy is described. If an amorphous alloy having a composition represented by the above composition formula can be obtained, the method for manufacturing an amorphous alloy is not limited. As described above, the alloy has the form of a thin strip, a thin sheet, a granular object, a block, etc. In order to obtain a desired form, the method for manufacturing an amorphous alloy can be appropriately selected.

[0075] As a method for manufacturing an amorphous alloy, for example, the following method can be cited: an ingot is prepared in advance so that the amorphous alloy has a composition represented by the above composition formula, and the molten liquid obtained by melting the ingot is rapidly cooled to obtain the amorphous alloy. In the case where there are elements that will be lost when the ingot is melted, an ingot having a composition that takes into account its loss amount is prepared in advance. In addition, when the ingot is crushed and melted, it is preferred to perform a homogenization heat treatment on the ingot before crushing.

[0076] The quenching method of the molten metal may be a conventional method, such as a single roll method using a cooling roll made of copper or a copper alloy. The circumferential speed of the cooling roll in the single roll method may be a standard circumferential speed in the case of manufacturing an amorphous alloy whose main component is Fe. The circumferential speed of the cooling roll may be, for example, generally 15 m / sec to 55 m / sec.

[0077] The temperature of the molten metal when discharged to the single roll is usually 50 to 300° C. higher than the melting point of the ingot. The atmosphere when the molten metal is discharged is not particularly limited, but an atmosphere of an inert gas is preferred from the viewpoint of reducing the mixing of oxides and the like into the amorphous alloy.

[0078] (Process of rapidly heat treating an amorphous alloy)

[0079] Next, the amorphous alloy is subjected to rapid heat treatment. The so-called rapid heat treatment means that the amorphous alloy is rapidly heated to a specified temperature range, maintained for a short time, and then rapidly cooled. Specifically, the amorphous alloy is heated at a heating rate of usually 100°C / second or more to a temperature range above the crystal formation start temperature of the α-Fe phase and below the Fe-B compound formation start temperature (in one embodiment, as described below, heated to a temperature range from a temperature usually 100°C higher than the crystal formation start temperature of the α-Fe phase to a temperature lower than the Fe-B compound formation start temperature, in one embodiment, heated to a temperature range from a temperature higher than 150°C to a temperature lower than the Fe-B compound formation start temperature, in one embodiment, heated to a temperature range from a temperature higher than 200°C to a temperature lower than the Fe-B compound formation start temperature), maintained in this temperature range for 0 seconds to 80 seconds, and then cooled at a cooling rate of usually 100°C / second or more.

[0080] If the heating rate is usually above 100°C / second, the crystalline phase will not coarsen. From the viewpoint of avoiding the coarsening of the crystalline phase, it is preferred that the heating rate is fast, so the heating rate is above 150°C / second in one embodiment, and above 325°C / second in one embodiment. On the other hand, if the heating rate is very fast, the heat source used for heating becomes too large, which impairs economic efficiency. From the viewpoint of the heat source, the heating rate is below 415°C / second in one embodiment. The heating rate may be the average rate from the start of heating until the start of holding. The heating rate may be the average rate from the start of heating until the start of cooling when the holding time is 0 seconds. Alternatively, the heating rate may be the average rate in a specific temperature range, such as between 100°C and 500°C.

[0081] If the holding time is more than 0 seconds, fine crystalline phases can be obtained from the amorphous phase. Furthermore, the so-called holding time of 0 seconds refers to cooling or terminating the holding immediately after rapid heating. The holding time is more than 3 seconds in one embodiment. On the other hand, if the holding time is less than 80 seconds, the coarsening of the crystalline phase can be avoided. From the viewpoint of avoiding the coarsening of the crystalline phase, the holding time is less than 60 seconds in one embodiment, and less than 10 seconds in one embodiment.

[0082] If the heat treatment temperature (holding temperature) is usually above the crystallization start temperature of the α-Fe phase, the amorphous phase can be turned into a crystal phase, and the generated nanocrystalline structure can be stabilized. On the other hand, if the holding temperature is above the Fe-B compound generation start temperature, strong crystal magnetic anisotropy is generated due to the generation of the Fe-B compound, and as a result, the coercive force increases. Therefore, by setting the holding temperature to be usually lower than the Fe-B compound generation start temperature, the crystal phase can be refined without generating the Fe-B compound. Therefore, the heat treatment temperature is in a temperature range above the crystallization start temperature of the α-Fe phase and lower than the Fe-B compound generation start temperature (in one embodiment, as described below, it is in a temperature range from a temperature higher than the crystallization start temperature of the α-Fe phase to a temperature lower than the Fe-B compound generation start temperature). In one embodiment, the heat treatment temperature is usually 485°C to 500°C. Furthermore, the crystallization start temperature of the α-Fe phase and the Fe-B compound generation start temperature may differ depending on the alloy system, but can be measured, for example, by DSC measurement. In addition, the heat treatment temperature is a temperature reached by the amorphous alloy through the heat treatment.

[0083] The heating method is not particularly limited as long as the amorphous alloy can be heated at the temperature increase rate described above.

[0084] When a normal atmosphere furnace is used, the temperature increase rate and / or the holding temperature of the atmosphere in the furnace can be made higher than the desired temperature increase rate and / or holding temperature for the amorphous alloy.

[0085] When an infrared furnace is used instead of a normal atmosphere furnace, the time difference between the heat input to the infrared heater and the heat received by the amorphous alloy can be reduced. In addition, the so-called infrared furnace is a furnace that uses a concave surface to reflect the light emitted by an infrared lamp to quickly heat the object to be heated.

[0086] In addition, the amorphous alloy may be rapidly heated and maintained by heat transfer between solids. For example, the amorphous alloy may be sandwiched between blocks that have been heated to a desired maintenance temperature to rapidly heat and maintain the amorphous alloy.

[0087] When the temperature reduction rate of the soft magnetic material is generally 100° C. / sec or more, and in one embodiment, 100° C. / sec to 415° C. / sec, the crystal phase will not further coarsen.

[0088] Although not being bound by theory, it is believed that when an amorphous alloy is subjected to rapid thermal treatment, the following phenomenon occurs in the amorphous alloy.

[0089] The amorphous alloy is quickly heated to a temperature range above the crystal formation start temperature of the α-Fe phase and is kept in this temperature range for a short time, so that it is considered that the coarsening of the microstructure of the crystalline phase can be avoided and the obtained crystalline phase is refined.

[0090] Here, the size of the microstructure depends on the heterogeneous nucleation rate, which is governed by the atomic transport and the size of the critical nucleus.

[0091] In order to make the microstructure finer, it is possible to consider increasing the heterogeneous nucleation rate. In order to increase the heterogeneous nucleation rate, it is possible to consider increasing atomic transport and reducing the size of the critical nucleus. In order to achieve these two conditions, it is effective to introduce a supercooled liquid zone in an amorphous solid. Since the viscous flow in the supercooled liquid zone in an amorphous solid is very large, the strain energy caused by nucleation in the supercooled liquid is much smaller than the strain energy caused by nucleation in the amorphous solid. Therefore, in the supercooled liquid zone, many embryos become nuclei.

[0092] However, in conventional heat treatment (annealing), the crystallization of amorphous materials starts from a relatively low temperature due to the slow heating rate. Therefore, at relatively low temperatures, the transition from solid to supercooled liquid is limited, and heterogeneous nucleation is also very limited.

[0093] In contrast, when heating is performed by rapid temperature increase as in the present invention, the crystal formation start temperature of the α-Fe phase in the amorphous alloy rises. Thus, the amorphous phase can maintain the amorphous state until a high temperature at which the amorphous phase vigorously changes into a supercooled liquid. If the amorphous phase changes into a supercooled liquid, the atomic transport becomes high, the critical nucleus size becomes small, and the heterogeneous nucleation rate becomes high. As a result, the nucleation frequency also becomes high.

[0094] Therefore, by rapidly raising the temperature of the amorphous alloy, high atomic transport can be achieved in the region where the supercooled liquid is generated, thereby causing active nucleation.

[0095] On the other hand, if the temperature of the amorphous alloy is raised rapidly, the grain growth rate also increases. In the present invention, since the holding time is short, the grain growth time is shortened and the grain growth is suppressed.

[0096] In addition, in the crystallization process, when the thermal energy applied to the amorphous alloy is insufficient (for example, the heat treatment temperature is low), the diffusion of atoms in the amorphous alloy becomes insufficient, and it can be considered that the heat treatment is completed in an unstable state. Therefore, for example, when the obtained soft magnetic material is used in a high temperature environment, the thermal energy applied from the use environment causes the movement of atoms in the material, and the short-range structure of the material changes, and as a result, there is a possibility that the magnetic properties of the material decrease, for example, the coercive force of the material increases.

[0097] Therefore, the alloy having an amorphous phase is heated to a temperature higher than the crystallization start temperature of the α-Fe phase, in particular, a temperature higher than the crystallization start temperature of the α-Fe phase, for example, usually 100° C. to 200° C., and in one embodiment, 100° C. to 150° C. As a result, the diffusion of atoms in the amorphous alloy is fully performed, and for example, even when the obtained soft magnetic material is used in a high temperature environment, the movement of atoms (mainly the movement of B atoms) caused by the thermal energy applied from the use environment can be suppressed, and as a result, the magnetic properties of the material are stabilized, in particular, the coercive force is stabilized to be kept at a low state.

[0098] On the other hand, when the temperature of the amorphous alloy reaches the Fe-B compound formation start temperature, the Fe-B compound is formed. The Fe-B compound has a large crystal magnetic anisotropy, thus increasing the coercive force.

[0099] Therefore, by heating the amorphous alloy to a temperature lower than the Fe—B compound formation start temperature, the formation of the Fe—B compound can be suppressed, and the properties, particularly the magnetic properties, can be maintained well.

[0100] Example

[0101] Hereinafter, some embodiments of the present invention will be described, but the present invention is not intended to be limited to the scope shown in these embodiments.

[0102] (Production of Amorphous Alloy)

[0103] The raw materials were weighed so as to have the composition shown in Table 1, and arc-melted to produce an ingot. As the raw materials, pure Fe, Fe-B alloy, pure Ni, etc. were used. In this process, the ingot was reversed and repeatedly melted (3 to 5 times) so as to become homogeneous.

[0104] The finely cut ingot is loaded into the nozzle of a liquid quenching device (single roller method), and melted by high-frequency heating in an inert atmosphere to obtain a molten metal. Then, the molten metal is discharged onto a copper roller with a circumferential speed of 30m / s to 70m / s for quenching, thereby obtaining an amorphous alloy in a strip shape with a width of 5mm. The temperature during discharge is set to the melting point + (50°C to 200°C). In addition, the quenching conditions are adjusted by setting the gap to 0.4mm and controlling the chamber pressure and the nozzle pressure so that the discharge pressure becomes 40kPa to 80kPa.

[0105] In addition, before the heat treatment described below, the amorphous alloy was confirmed to be amorphous by XRD and its composition was confirmed by ICP.

[0106] (Heat treatment of amorphous alloys)

[0107] The amorphous alloy having the composition described in Table 1 was sandwiched between a heating plate and a calcium silicate plate in such a manner as to form a heating plate (made of stainless steel)-amorphous alloy-calcium silicate plate, and then heated for 3 seconds, and then rapidly cooled by separating from the heating plate, wherein the heating plate was heated in such a manner that the temperature of the amorphous alloy became the heat treatment temperature described in Table 1. By this heating, the amorphous phase in the amorphous alloy was crystallized to prepare a sample of a soft magnetic material. In addition, the heating rate was 100°C / second or more, and the cooling rate was 100°C / second.

[0108] (Evaluation of Samples)

[0109] For each heat-treated sample, XRD (device: Rigaku SmartLabII) analysis was performed under the conditions described in Table 2 to calculate the area ratio of each peak of the α-Fe phase. The area ratio of each peak was calculated according to the above method. Thereafter, for each heat-treated sample, VSM (vibrating sample magnetometer)-P2H-Helmholtz coil 2000e (manufactured by Toei Industry Co., Ltd.) was used to measure the coercive force and saturation magnetic flux density.

[0110] In Table 1 and Figures 1 to 3 The results are shown in . Figure 1 Regarding the samples with a heat treatment temperature of 490°C (Example 5 and Comparative Examples 5 to 6), the relationship between the Si content and (A) the crystalline (211) plane peak area ratio or (B) the saturation magnetic flux density is shown. Figure 2 Regarding the samples having a Si content of 0.8 atomic % (Examples 1 to 7 and Comparative Examples 1 to 4), the relationship between the heat treatment temperature and the saturation magnetic flux density is shown. Figure 3 Regarding the sample with a Si content of 0.8 atomic %, the relationship between the crystalline (211) plane peak area ratio and the saturation magnetic flux density is shown.

[0111] Table 1

[0112]

[0113] Table 2 XRD measurement conditions

[0114]

[0115] In Table 1, amo represents an amorphous peak. Figure 1 It can be seen that by containing an appropriate amount of Si, the crystalline (211) plane peak area ratio can be increased, thereby increasing the saturation magnetization. Figure 2 It can be seen that when manufacturing the soft magnetic material of the present invention, the crystalline (211) plane peak area ratio can be controlled by rapid heat treatment, especially the heat treatment temperature. Figure 3 It is found that, in the soft magnetic material of the present invention, the saturation magnetization can be increased by increasing the crystalline (211) plane peak area ratio.

Claims

1. A soft magnetic material having the following composition formula: Fe 100-x-y-z-w B x Ni y Si z M w A soft magnetic material represented by: wherein M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co and Sn, and x, y, z and w, in terms of atomic %, satisfy 12≤x≤17, 1≤y≤3, 0 <z≤1、0<w≤0.1, The soft magnetic material contains α-Fe phase, The α-Fe phase contains crystals with an average particle size of 30 nm or less. The average grain size of the crystal is the average value of the equivalent circular diameter of the crystal projection area in the transmission electron microscope (TEM) image of the soft magnetic material sliced ​​by focused ion beam (FIB). The ratio of the peak area of ​​the (211) plane of the crystalline α-Fe phase on the surface of the soft magnetic material measured by XRD to the area of ​​the entire peak is 0.10 or more.

2. The soft magnetic material according to claim 1, 0.2≤z≤0.

9.

3. A method for manufacturing a soft magnetic material, comprising the following steps: Prepare an alloy having the following compositional formula: Fe 100-x-y-z-w B x Ni y Si z M w and having an amorphous phase, where M is one or more inevitable elements selected from Nb, Mo, Ta, W, Co, and Sn, and x, y, z, and w satisfy 12 ≤ x ≤ 17, 1 ≤ y ≤ 3, 0 < z ≤ 1, 0 < w ≤ 0.1 in atomic percentages; and The alloy is subjected to rapid heat treatment in such a manner that the alloy reaches a temperature in a temperature range that is not less than a crystal formation start temperature of an α-Fe phase and less than a Fe—B compound formation start temperature. 4 . The method for producing a soft magnetic material according to claim 3 , wherein the alloy reaches a temperature of 485° C. to 500° C. in the rapid thermal treatment. 5 . The method for producing a soft magnetic material according to claim 4 , wherein in the rapid thermal treatment, the heating rate of the alloy is 100° C. / sec to 415° C. / sec. 6 . The method for producing a soft magnetic material according to claim 5 , wherein in the rapid thermal treatment, the alloy is held for a time of 0 to 80 seconds. 7 . The method for producing a soft magnetic material according to claim 3 , wherein the rapid thermal treatment is performed by sandwiching the alloy between heated blocks.

Citation Information

Patent Citations

  • Fe-base soft-magnetic alloy

    JP1994041698A

  • Method for manufacturing soft magnetic material

    JP2018022797A

  • Soft magnetic material and production method of the same

    JP2019206746A